Efektivitas Inovasi Program Bank Sampah (Gerbang Sampah) di Kota Malili - Ahmad Taufik (Kolaborasi : Jurnal Administrasi Publik, 2021)
Innovation Waste bank is the concept of dry and sorted waste collection and has management like banking, but saved not money but garbage. The purpose of this study is to find out the Effectiveness of Innovation of Waste Bank Program (Garbage Gate) in Malili City. The research method used is qualitative descriptive that describes problems related to events that appear around researchers, and the type of research used is phenomenology that is researching an event or event that occurs in the present. The data sources used are primary data sources and secondary data with informants of 7 people. Data collection techniques using interviews, observations, and documentation. Data analysis techniques used are data reduction, data collection, and conclusion drawing. The results of the research conducted show several indicators in the form of innovation products, namely with the innovation of waste bank programs can reduce the burden of janitors, the process of innovation that is in the process of hiring waste bank administrators really people who care about the environment, the quality of innovation that is in achieving the quality of innovation needs to be the role and cooperation of the community. As for the factors that affect the effectiveness of innovation of waste bank programs, namely limited facilities and prasana due to the lack of budget from the government, human resources can change the pattern of community piker in maintaining the environment. Keywords: innovation, waste bank, community participation